Medicina regenerativa en odontología. 2019 - Washington Geovanny, Melena Moyota (2021)
The purpose of this research was to describe the usefulness of stem cells in the regeneration of dental tissues and the body and to identify the main applications of regenerative medicine in the different areas of dentistry, recognizing its limitations. The research was developed through the bibliographic review of scientific articles found in PubMed, Google Scholar, and Elsevier during the last ten years. Seventy-five articles were compiled, of which those with an average ACC citations count were selected, in addition to the articles whose journal was in the Scimago Journal Raking, finally 65 articles were obtained for the systematic review. After analyzing the literature, it was found that the study of stem cells in dentistry focused on oral epithelial and mesenchymal stem cells, which participated in the reconstruction of the organism's epithelia, the formation of the dentin-pulp complex, and the periodontal ligament, bone, muscle, tendon, cartilage, neural tissue. Regenerative medicine applications could be distinguished in areas such as endodontics, periodontics, oral and maxillofacial surgery. The administration of growth factors, microvascular reconstruction, pulp, bone, and periodontal regeneration, was demonstrated through tissue bioengineering. The limitations of the subject were recognized as the lack of clinical trials in humans that corroborate the theory that exists at the moment and the oncogenic potential that can be generated in cells and the high cost of these treatments.